2018
DOI: 10.1128/jvi.01466-17
|View full text |Cite
|
Sign up to set email alerts
|

Early Epstein-Barr Virus Genomic Diversity and Convergence toward the B95.8 Genome in Primary Infection

Abstract: Over 90% of the world's population is persistently infected with Epstein-Barr virus. While EBV does not cause disease in most individuals, it is the common cause of acute infectious mononucleosis (AIM) and has been associated with several cancers and autoimmune diseases, highlighting a need for a preventive vaccine. At present, very few primary, circulating EBV genomes have been sequenced directly from infected individuals. While low levels of diversity and low viral evolution rates have been predicted for dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…Sequencing the BZLF1 open reading frame and miniZp promoter thereof in our complete virus panel revealed that all of them are within the western group and 21/22 viruses are within the B95-8 subgroup and lack the Zp-V3 polymorphism. This fits with previous reports showing that patients with IM carry viruses that are very closely related to B95-8 (36). However, the replicating abilities of these strains widely varied, suggesting that polymorphisms outside of BZLF1 modulate this property.…”
Section: B-cells Infected By Rm81 or Rmshj Are Responsive To A Btk-spsupporting
confidence: 92%
“…Sequencing the BZLF1 open reading frame and miniZp promoter thereof in our complete virus panel revealed that all of them are within the western group and 21/22 viruses are within the B95-8 subgroup and lack the Zp-V3 polymorphism. This fits with previous reports showing that patients with IM carry viruses that are very closely related to B95-8 (36). However, the replicating abilities of these strains widely varied, suggesting that polymorphisms outside of BZLF1 modulate this property.…”
Section: B-cells Infected By Rm81 or Rmshj Are Responsive To A Btk-spsupporting
confidence: 92%
“…Target enrichment of EBV genomes has enabled the high-throughput sequencing of whole EBV genomes from infected cells and biospecimens to reveal genetic diversity, which is greatest in the latent genes (35). There is early evidence supporting the notion that the diversity of EBV genomes within an infected individual is highest during early infection and steadily decreases during establishment of chronic infection and latency (42). Studies of EBV populations circulating in the peripheral blood and oral lavage fluids of asymptomatic carriers also demonstrate that EBV populations are compartmentalized (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that EBV genome usually underwent clonal expansion in NPC tumors or other malignancies 26,27,32 . In the scenario of clonal expansion, EBV genome is stable and intra-host mutation rate is often low, and heterozygous variants as a result of quasi-species evolution within a host are not frequent 12,18,33 . On the contrary, EBV isolates from specimens with multiple infections will have a higher number of heterozygous variants.…”
Section: Methodsmentioning
confidence: 99%